The Grammatical Status of the Adjectival Forms Gera, Gražu - Tekorienė, Dalija (Kalbotyra, 1987)
The paper considers four alternative treatments of the grammatical status of the adjectival forms gera, gražu which occur in Lithuanian grammars: as the neuter forms of the adjective, adverbs, statives, and the non-gender forms of the adjective. It is argued that the existence and use of these forms, just as the existence and use of the masculine and feminine forms, can be explained adequately by laws of syntactic agreement. Masculine and feminine adjectival forms are used when the grammatical subject is a nominal with some gender meaning, i. e. a noun or a pronoun, forms with the ending -a, -u are used predicatively in subjectless clauses or when the position of the grammatical subject is filled by a nominal which does not possess any meaning of gender, i. e. an infinitive, a non-gender pronoun, a subordinate clause or some other phrase. It is logical, therefore, to treat the forms gera, gražu as the non-gender forms of the Lithuanian adjective.